HUBUNGAN ASUPAN SERAT MAKANAN DAN AIR DENGAN POLA DEFEKASI ANAK SEKOLAH DASAR DI KOTA BOGOR - Ambarita, Elyzzabeth Mayorga; Madanijah, Siti; Nurdin, Naufal Muharam (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The study aimed to analyze correlation between dietary fiber and water intake with defecation pattern among elementary school students. A Cross-sectional design was used in this study. Subjects were 527 students of V and VI grades. The results showed that the mean of fiber and water intake of students was categorized as low. The average dietary fiber intake was 12.4 g/d. The average water intake was 1 086 ml. The average frequency of bowel movements was six times/week with the consistency of the stool according to Bristol Stools Chart categories was normal (type 4). Based on correlation test, there was significant correlation between fiber intake with stool frequency and consistency of stool (p<0.05). However, there was no significant correlation between fiber intake with painfulness during defecation, water intake with stool frequency, consistency of stool, painfulness during defecation, and constipation (p>0.05).